ε-Polylysine inhibits Alternaria alternata through membrane-targeted antifungal activity and N-glycosylation modification - Wenhui Xu; Min Wang; Hao Jiang; Yangyang Sun; Yamin Du; Maorun Fu (Postharvest Biology and Technology, 2026)

From molecular assembly to functionality: structural characterization of chestnut 11S globulin and its implications for thermal gelation and bioactive peptide release - Haoxin Cui; Ying Zhang; Dongze Qin; Fan Wei; Zhenting Yu; Sihao Wu; Yazhou Ji; Wenhui Fu; Yan Zhang; Ruican Wang; Shuo Wang (Food Hydrocolloids, 2026)

Mechanistic investigation of sucrose monostearate-mediated antifungal effects against Penicillium oxalicum - Yanru Sun; Jing Gao; Xianrui Jin; Shuhan Li; Yexuan Hou; Lu Fu; Wenhui Zhang (Archives of Microbiology, 2026)

Ultrasound-microwave synergistic treatment modulates highland barley dough structure and bread quality characteristics - Xiaolu Wu; Liping Fu; Xinyi Chen; Sizhe You; Wenhui Zhang; Liangfeng Ma; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Research International, 2026)

Cell-free Lacticaseibacillus rhamnosus-fermented cereal fraction attenuates 5-fluorouracil-induced intestinal mucositis in mice: Associations with redox homeostasis and epithelial structural preservation - Wenhui Fu; Xuemeng Ji; Dongze Qin; Lingda Zhao; Huan Lv; Yaozhong Hu; Ruican Wang; Wentao Gu; Dongfei Tan; Shuo Wang (Food Bioscience, 2026)

Multi-objective optimization of PEMFC performance based on the stacking model and multi-population multi-objective gray wolf optimizer - Guanjie Zhang; Wenhui Xu; Jianqin Fu; Jinbo Kuang; Xilei Sun (Chemical Engineering Journal, 2026)

Network toxicology and multi-omics reveal the mechanism of testicular toxicity induced by chronic AFB1 exposure in male quails - Zhenlei Ping; Yu Wang; Linlin Fu; Xiaoying Cui; Songtao Zheng; Xiaowen Jiang; Wenhui Yu (Journal of Hazardous Materials, 2026)

BiOI/Bi4O5Br2/BiOBr double S-scheme heterostructure applied in photocatalysis antimicrobial and degradation: mechanisms and pathways - Liying Huang; Kaixiang Sun; Li Qiu; Yeping Li; Yanyan Fu; Jun Huang; Wenhui Bian; Lijing Huang (Environmental Research, 2026)

Designing enzyme-CNC brick-and-concrete structured PLA film for photothermal regulation and agricultural protection applications with stage-dependent degradation - Wenhui Fu; Duo Yu; Aiping Zhan; Hou-Yong Yu (Journal of Hazardous Materials, 2026)

Molecular orchestration of highland barley starch-β-glucan complexes under extrusion thermomechanics: linking hierarchical structure to digestive resistance - Liping Fu; Yingting Zhao; Xinyi Chen; Lujie Cheng; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Research International, 2026)

Glycyrrhizic acid nanofibrils as potent ice recrystallization inhibitors: mechanism and application in ice cream - Zhanghanyu Liu; Yinling Liu; David Everett; Yun Zhai; Wenhui Qi; Yuying Fu; Teng Li (Food Research International, 2026)

Corrigendum to “Interplay of quorum-sensing signals (homoserine lactone/penicillic acid) and nitrate in regulating microbial processes: As(III) immobilization, CH4 and N2O emission in constructed wetlands” [Biores. Technol. 455 (2026) 134788] - Dongxue Fu; Wenhui Ma; Jing Zhang; Honghui Wang; Yixin Wu; Liyun Ge; Chunzhen Fan; Shuqing Wu; Shuyun Zhang; Hui Gao; Zheng Chen (Bioresource Technology, 2026)

From economic crop to high-value product: Fermentation of chestnut protein by Lactobacillus rhamnosus ameliorates chronic inflammation via the gut microbiota–SCFAs axis - Dongze Qin; Wenhui Fu; Haoxin Cui; Haiwei Liu; Hang Yang; Yaozhong Hu; Ruican Wang; Xuemeng Ji; Shuo Wang (International Journal of Food Microbiology, 2026)

Partial debranching and microwave treatment stabilize amylopectin-flavor interactions for better tsampa processing outcomes - Xinyi Chen; Liping Fu; Ye Xu; Lujie Cheng; Zijian Huang; Wenhui Zhang; Qisen Xiang; Yang Liu; Yuting Tian; Yingting Zhao (Carbohydrate Polymers, 2026)

A comparative study on the developmental toxicity of three dihydroxynaphthalene positional isomers in zebrafish embryos - Zijian Li; Ke Xu; Ziang Wang; Wenhui Zhi; Die Fu; Xiying Zhou; Weitao Hu; Zhonghao Xiao; Zigang Cao; Huimin Li; Xiaowen Shi (Toxicology and Applied Pharmacology, 2026)

Spatial–spectral feature guidance network for fine-grained object detection and recognition on complex-valued SAR images - Yuxi Suo; Youming Wu; Wenhui Diao; Qingbiao Meng; Xian Sun; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Mechanisms underlying the loss of anti-inflammatory activity in honey-processed licorice: a process–structure–function approach - Wenhui Jing; Sijin Xu; Cunbing Li; Yuxing Li; Xiaoyun Li; Hong Sui; Xueyan Fu (Food Chemistry, 2026)

A Compact, Universal Fusion Tag Enables Robust Expression of Challenging Enzymes for Starch Bioconversion and Optimized Metabolism in Bacillus subtilis - Yuqiao Wang; Jinlong Li; Wenhui You; Xuyang Huang; Miaomiao Xia; Jing Qiao; Tao Cai; Ziqing Gao; Gang Fu; Dawei Zhang (Bioresource Technology, 2026)

Oil Slick Detection in X-Band Marine Radar Imagery: Leveraging a Boundary-Aware SBR Feature and an Improved Whale Optimization Algorithm - Jianxun Rui; Jin Xu; Jianbin Yuan; Zekun Guo; Shuo Zhang; Yiteng Zhang; Qiuyu Fu; Boxi Yao; Yulong Yang; Wenhui Li (Journal of Marine Science and Engineering, 2026)
Marine oil spills pose a persistent threat to marine ecosystems and coastal economies, and their rapid and unpredictable spread requires timely and reliable monitoring. In X-band marine radar images, oil slicks usually appear as low-contrast dark targets embedded in heterogeneous sea clutter, making accurate segmentation particularly challenging. To address this problem, this study proposes a training-free two-stage oil slick detection framework that combines an improved Slick Boundary Ratio (SBR) feature with an improved Whale Optimization Algorithm (WOA). First, the improved SBR feature is used to extract the oil slick region of interest (ROI). Then, the improved WOA is employed to determine the global threshold for oil slick segmentation. Experimental results show that the proposed method achieves accurate and spatially coherent oil slick segmentation in complex radar backgrounds, with an Accuracy of 99.36%, a Precision of 85.73%, a Recall of 84.42%, an F1-score of 85.07%, and an Intersection over Union (IoU) of 74.01%. These results indicate that the proposed framework can effectively suppress false positives while maintaining strong detection sensitivity, thereby improving segmentation robustness in low-contrast marine radar scenes. Owing to its training-free design, the proposed method shows potential for shipborne and coastal oil spill monitoring applications.

One-step conversion into Al2O3 coated Si nanowire anode from photovoltaic silicon waste wafers through electrothermal shock for excellent capacity retention - Qiushi Chen; Xuzhong Gong; Wenhui Fu; Xiaorui Wang; Junhao Liu; Zhi Wang (Resources, Conservation and Recycling, 2026)

Comprehensive assessment of hydrolyzed pig hoof keratin (HPHK) as a potential food ingredient: Stability, techno-functional properties, in vitro, and in silico bioactivities - Ruican Wang; Ying Zhang; Haoxin Cui; Wenhui Fu; Dongfei Tan; Qisijing Liu; Xuemeng Ji; Liye Zhu; Shuo Wang (Food Chemistry, 2026)

Nuclear protein 1 defends against acute pancreatitis by mitigating pancreatic acinar cell ferroptosis through the maintenance of cellular iron homeostasis - Xiangtian Zeng; Wenhui Chen; Qixin Dai; Yong He; Xinsong Fu; Jiaxin Liu; Dingwen Zhong; Yonghui Liao (Toxicology and Applied Pharmacology, 2026)

A centrifugal speed-based method for controlling debranched products of highland barley amylopectin distribution and isolating long-branched chains - Xinyi Chen; Can Zhao; Yang Liu; Liping Fu; Wenhui Zhang; Qisen Xiang; Yuting Tian; Yingting Zhao (Food Hydrocolloids, 2026)

Integration of transcriptomic and metabolomic data reveals the low temperature response gene regulatory network of germination in soybean (Glycine max L.) - Wenhui Fu; Jingying Nie; Junli Ou; Yuchen Liu; Benshi Zhou; Yan Jing; Yonggang Zhou; Junlong Gao; Keheng Xu; Chen Feng; Hongtao Gao; Yaxin Li; et al. (Plant Science, 2026)

Effects of high-moisture extrusion technology on structural properties, physicochemical properties and in-vitro starch digestibility of highland barley (Zangqing 3000) flour - Liping Fu; Yingting Zhao; Can Zhao; Yang Liu; Yixin Zheng; Yingying Yan; Qisen Xiang; Wenhui Zhang; Yuting Tian (Food Chemistry, 2025)

Study of DBN-based deep eutectic solvents for CO2 capture: the effects of three different hydrogen bond donors - Hui Fu; Wenhui Yue; Menghan Yuan; Yutong Wang; Xinming Zhou (Journal of Environmental Chemical Engineering, 2025)

Ortho-N-S/N-O dual-site synergistic COF for efficient selective removal and highly sensitive detection of hydrated lead ions - Huizhen Sun; Xiuhua Chen; Zongdeng Wu; Wenhui Ma; Shaoyuan Li; Chen Li; Dandan Wu; Kaixin Fu; Kexiang Ding (Chemical Engineering Journal, 2025)

Constructing WO3/g-C3N4/BiOBr as efficient dual Z-scheme heterojunction nanocomposite for LED light-driven inactivation of bacteria - Yanyan Fu; Shuangxiu Shu; Jun Huang; Wenhui Bian; Lijing Huang; Liying Huang; Yeping Li (Journal of Water Process Engineering, 2025)

Overcoming microbial antagonism: strategic enhancements for dibenzofuran bioremediation - Yanan Wu; Changai Fu; Yan Chen; Xu Wang; Wenhui Zhao; Meng Chen; Li Li (Journal of Environmental Management, 2025)

The roles of NLRP3 and prostaglandin E2 in mediating bidirectional cross-talk between bovine endometrial fibroblasts and M2 macrophages - Jiamin Zhao; Haixia Bao; Wenhui Bao; Zhiguo Gong; Yunhe Fu; Xiaoyu Hu; Yanqin Dong; Wei Mao; Shuang Feng; Shuangyi Zhang (Animal Reproduction Science, 2025)

Dynamics and secondary pollution risk assessment of heavy metals during Sargassum polycystum floating and decomposing process - Yuzhong Fu; Jinling Li; Sunlin Fu; Yunquan Wu; Wenhui Yu; Songguang Xie; Hongtian Luo (Algal Research, 2025)

Upcycling waste cartons into an efficient Fenton-like chainmail catalyst CoOx@C: Process, performance, and mechanism - Chen-Xuan Li; Wenhui Xu; Bai Li; Xiangyang Xu; Xian-Zhong Fu; Rui Deng; Feng Zhang; Yimin Sun; Kangping Cui (Journal of Environmental Chemical Engineering, 2025)

Amyloid protein fibrils serve as an ice recrystallization inhibitor for ice cream - Shengjie Gao; Shuo Liu; Zhanghanyu Liu; Mengting Wang; Wenhui Qi; Yuying Fu; Teng Li (Food Hydrocolloids, 2025)

Lattice-matched MnxCd1-xS@MnS heterojunction photocatalysts: High-intensity built-in electric field boosts photocatalytic U(VI) reduction - Xueting Lv; Xin Huang; Xiang Li; Xiaoying Duan; Jiajing Wu; Wenhui Shi; Chuantao Wang; Yanzhong Zhen; Feng Fu (Journal of Water Process Engineering, 2025)

Feasibility analysis of China's CO2-EOR project based on a comprehensive economic benefit evaluation across the entire industrial chain - Chuanwang Liu; Yalin Lei; Wenhui Chen; Yong Jiang; Jingrui Fu (Journal of Environmental Management, 2025)

Lactobacillus paracasei GF027 promotes growth and cognitive development in juvenile rats via regulating intestinal microecology and nourishing the brain - Hang Yang; Yuanyifei Wang; Haiwei Liu; Jin Wang; Dancai Fan; Yi Sun; Huan Lv; Wenhui Fu; Shuo Wang (Food Bioscience, 2025)

The rapid fermentation of Euphausia superba sauce and revealing of the relationship between key flavor compounds and core microorganisms - Wenhui Qu; Lihao Wang; Qing Kong; Ruoshu Li; Weijia Liu; Zhanfei Fu; Yunqi Wen; Changhu Xue (Food Research International, 2025)

Computer-aided design and construction of a novel electro-responsive ion-imprinted sensor for the individual/simultaneous detection of Cd(II) and Pb(II) in water environments - Kaixi Fu; Huizhen Sun; Xiuhua Chen; Yilin Cao; Longsi Liu; Junnan Zhao; Shaoyuan Li; Wenhui Ma (Food Chemistry, 2025)

Associations between dietary carotenoid and biological age acceleration: insights from NHANES 2009–2018 - Xinyun Chen; Chunying He; Wenhui Yu; Liang Ma; Shenju Gou; Ping Fu (Biogerontology, 2025)

Two-step interfacial reaction to design robust cellulose-based films with excellent hydrophobicity and self-cleaning features for single-use delivery bags - Wenhui Fu; Somia Yassin Hussain Abdalkarim; Chengling Huang; Yanjuan Dong; Hou-Yong Yu (Journal of Cleaner Production, 2025)

Computer-aided design and preparation of surface arsenite molecularly imprinted polymers for selective adsorption and highly sensitive detection of As(Ⅲ) - Kaixi Fu; Huizhen Sun; Xiuhua Chen; Longsi Liu; Yilin Cao; Junnan Zhao; Shaoyuan Li; Wenhui Ma (Journal of Hazardous Materials, 2024)

Chestnut protein as functional ingredients in gluten-free products: Evaluation of nutritional properties in native and fermented forms - Wenhui Fu; Dongze Qin; Haoxin Cui; Sihao Wu; Ruican Wang; Yaxiong Song; Qiang Xie; Xuemeng Ji; Huan Rao; Shuo Wang (Food Bioscience, 2024)

Comprehensive evaluation of phosphate deficiency tolerance in common vetch germplasms and the adaption mechanism to phosphate deficiency - Wenhui Yan; Ping Lu; Yuyan Liu; Zigang Hou; Liran Fu; Jia Shi; Guo Zhenfei; Haifeng Zhu (Journal of Plant Physiology, 2024)

Hydrophobic carbon quantum dots with Lewis-Basic nitrogen sites for electrocatalyst CO2 reduction to CH4 - Shuai Fu; Bijun Tang; Zeming Wang; Guangbin An; Mingwan Zhang; Kang Wang; Wenhui Liu; Huazhang Guo; Baohua Zhang; Liang Wang (Chemical Engineering Journal, 2024)

A green europium-cerium redox flow battery with ultrahigh voltage and high performance - Yating Wu; Lei Zhou; Yangyang Xie; Yaobin Lai; Shangwan Fu; Xingchen Kang; Wenhui Shi; Jian Li; Xuxia Zhang; Kang Hu; Hui Zhang; Tao Qi (Chemical Engineering Journal, 2024)

Trace iron induced piezo-polarization field strength on piezo-promoted peroxymonosulfate activation for pollutant degradation - Wangchuan Zhu; Chuantao Wang; Xiang Li; Wenhui Shi; Qiyu Chen; Xinlei Bai; Feng Fu; Danjun Wang; Chunming Yang (Chemical Engineering Journal, 2024)

HMGA1 Regulates IRS2 to Promote Inflammatory Responses and Oxidative Stress Injury in MPP+-Induced cells - Dongxun Xu; Wenhui Fan; Bing Fu; Hongxia Nie (Cell Biochemistry and Biophysics, 2024)

The synthesis of papaya fruit flavor-related linalool was regulated by CpTPS18 and CpNAC56 - Yuan Yao; Wenhui Fu; Yue Yu; Suyan Wan; Wenping Zhang; Ray Ming (Plant Reproduction, 2024)

Disorders of the small intestinal microenvironment in ovalbumin-sensitized mice and mitigation strategies of 2′-fucosyllactose and Bifidobacterium longum subsp. Infantis - Wenhui Fu; Ruixin Kou; Huan Lv; Jin Wang; Qiang Xie; Dongze Qin; Bowei Zhang; Huan Rao; Yang Tian; Shuo Wang (Food Bioscience, 2024)

Phase separation and gelation of gelatin-glucose syrup mixtures and gummy confections: Effects of moisture content, sugars, citric acid, and citrates - Ruican Wang; Richard W. Hartel; Xinyu Zhai; Wenhui Fu; Yi Sun; Shuo Wang (Food Hydrocolloids, 2024)

Sources, trigger points, and effect size of associations between PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) and fractional exhaled nitric oxide (FeNO): A panel study with 16 follow-up visits over 4 years - Yucong Fu; Wenhui Jia; Ningyu Zhang; Zhiyu Wang; Nan Zhang; Tong Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Xumei Zhang; et al. (Chemosphere, 2024)

Metabolic cross-feeding between the competent degrader Rhodococcus sp. strain p52 and an incompetent partner during catabolism of dibenzofuran: Understanding the leading and supporting roles - Xudi Wang; Yanan Wu; Changai Fu; Wenhui Zhao; Li Li (Journal of Hazardous Materials, 2024)

Porous hydrochar loaded nZVI as an efficient catalyst to activate persulfate for phenol degradation: Performance and mechanism - Bo Cao; Jianhua Qu; Wenhui Bian; Qiqi Hu; Xinyan Fu; Guangshan Zhang; Yuezhi Zhang; Yue Tao; Zhao Jiang; Ying Zhang (Journal of Cleaner Production, 2024)

Impact of antioxidants on PM2.5 oxidative potential, radical level, and cytotoxicity - Yixiang Wang; Chunbo Xing; Baohua Cai; Wenhui Qiu; Jinghao Zhai; Yaling Zeng; Antai Zhang; Shao Shi; Yujie Zhang; Xin Yang; Tzung-May Fu; Huizhong Shen; et al. (Science of The Total Environment, 2024)

Ambient PM2.5-bound polycyclic aromatic hydrocarbons (PAHs) associated with pro-thrombotic biomarkers among young healthy adults: A 16 times repeated measurements panel study - Wenhui Jia; Yucong Fu; Nan Zhang; Ningyu Zhang; Tong Wang; Zhiyu Wang; Nan Zhang; Jia Xu; Xueli Yang; Qiang Zhang; Changping Li; Xumei Zhang; et al. (Science of The Total Environment, 2024)

Mechanism of carbohydrate and protein conversion during sourdough fermentation: An analysis based on representative Chinese sourdough microbiota - Wenhui Fu; Shuo Wang; Wentong Xue (International Journal of Food Microbiology, 2024)

Adverse effects of plastic leachate and its component 2,4-DTBP on the early development of zebrafish embryos - Aifeng Li; Chen Yan; Jiangbing Qiu; Ying Ji; Yilei Fu; Wenhui Yan (Science of The Total Environment, 2023)

Graphene nanonetwork embedded with polyaniline nanoparticles as anode of Li-ion battery - Haiyang Fu; Bo Gao; Yuan Qiao; Wenhui Zhu; Zhuang Liu; Gaoyu Wei; Zhongbao Feng; Ali Reza Kamali (Chemical Engineering Journal, 2023)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Growing season temperature and precipitation affect nutrient resorption in herbaceous species through a foliar stoichiometric control strategy - Xiaowei Liu; Youqi Wang; Wenhui Fu; Zhiyou Yuan; Qiang Yu; Changhui Peng; Sally E. Koerner; Liang Guo (Plant and Soil, 2023)

Discovery and identification of a novel canine coronavirus causing a diarrhea outbreak in Vulpes - Yuting Liu; Yao Deng; Sheng Niu; Na Zhu; Jingdong Song; Xiaoshuang Zhang; Weiting Su; Wenhui Nie; Roujian Lu; David M. Irwin; George Fu Gao; Wenling Wang; et al. (Science Bulletin, 2023)

Knockout of SlbZIP68 reduces late blight resistance in tomato - Wenhui Yang; Chunxin Liu; Qingjun Fu; Xinyi Jia; Liping Deng; Chunying Feng; Yuhan Wang; Zhenru Yang; Huanhuan Yang; Xiangyang Xu (Plant Science, 2023)

Heterojunction reconstruction via In doping towards high-efficiency CZTSSe solar cells - Changcheng Cui; Junjie Fu; Dongxing Kou; Yimeng Li; Hao Wei; Zucheng Wu; Wenhui Zhou; Zhengji Zhou; Shengjie Yuan; Yafang Qi; Shuping Pang; Zhipeng Shao; et al. (Chemical Engineering Journal, 2023)

Coupling the digital twin technology and life cycle assessment: Carbon dioxide emissions from polysilicon production - Shengqiang Yang; Zhiqiang Yu; Wenhui Ma; Lin Ma; Chaochun Li; Ling Fu; Ming Li; Zewen Zhao; Yuchen Yang (Sustainable Production and Consumption, 2023)

Photocatalytic degradation of bisphenol A by temperature-sensitive magnetic hydrogel with enhanced service life - Wenhui Chen; Wei Mao; Zhiqiang Liu; Weilin Hou; Naresh Kumar; Jun Sun; Xingwei Cai; Cheng Huang; Wei Shen; Fu Yang; Yanjuan Cui; Hian Kee Lee; et al. (Journal of Hazardous Materials, 2023)

Retraction notice to “Transformer-induced graph reasoning for multimodal semantic segmentation in remote sensing” [ISPRS J. Photogramm. Remote Sens. 193 (2022) 90-103] - Qibin He; Xian Sun; Wenhui Diao; Zhiyuan Yan; Dongshuo Yin; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Intestinal microenvironment-mediated allergic dynamic phenotypes and endotypes in the development of gluten allergy - Qiang Xie; Chenglong Liu; Wenhui Fu; Chen Chen; Shimin Gu; Dan Luo; Wentong Xue (Food Research International, 2023)

Impact of particle size of cell carrier on caproate fermentation in a cell immobilized system: Focusing on the improvement of caproate production in batch and continuous operation modes - Yuxuan Sun; Jiaqi Fu; Yan Liu; Wenhui Zhang; Chengmei Li; Hossain M. Zabed; Mei Zhao; Weimin Liu; Shuhao Huo; Cunsheng Zhang; Xianghui Qi (Chemical Engineering Journal, 2023)

Effects of benthic fish and light regimes on water quality and the growth of Vallisneria natans with two sediment types - Hong Su; Wenhui Zheng; Mingfan Li; Chao Wang; Guanbao Fu; Ruijie Le; Gang Sun (Environmental Science and Pollution Research, 2023)

Cell cycle of microalga Isochrysis galbana arrested by neurotoxin β-N-methylamino-l-alanine and corresponding molecular mechanisms - Aifeng Li; Jianwei Liu; Jiangbing Qiu; Guixiang Wang; Xianyao Zheng; Ying Ji; Guowang Yan; Peng Zhao; Xizhen Wu; Wenhui Yan; Lei Zhang; Min Li; et al. (Science of The Total Environment, 2023)

Amyloid protein fibrils show enhanced ice recrystallization inhibition activity when serve as pickering emulsion stabilizer - Yuying Fu; Yuan Li; Shuni Weng; Wenhui Qi; Huanhuan Su; Teng Li (Food Hydrocolloids, 2023)

Degradation of levofloxacin in wastewater by photoelectric and ultrasonic synergy with TiO2/g-C3N4@AC combined electrode - Zihao Xing; Zijing Wang; Wenhui Chen; Manying Zhang; Xiaofei Fu; Yong Gao (Journal of Environmental Management, 2023)

Sourdough yeast-bacteria interactions results in reduced immunogenicity by increasing depolymerization and hydrolysis of gluten - Wenhui Fu; Xin Jia; Chenglong Liu; Xiao Meng; Ke Zhang; Sha Tao; Wentong Xue (Innovative Food Science & Emerging Technologies, 2023)

Identification and hepatoprotective activity of total glycosides of paeony with high content of paeoniflorin extracted from Paeonia lactiflora Pall - Lin Peng; Zhe Ma; Wenhui Chu; Peisi Jiang; Yongqian Fu; Pan Wang (Food and Chemical Toxicology, 2023)

Defect engineering enabling p-type Mo(S,Se)2:TM (TM = V, Nb, Ta) towards high-efficiency kesterite solar cells - Junjie Fu; Afei Zhang; Dongxing Kou; Zewen Xiao; Wenhui Zhou; Zhengji Zhou; Shengjie Yuan; Yafang Qi; Zhi Zheng; Sixin Wu (Chemical Engineering Journal, 2023)

Height aware understanding of remote sensing images based on cross-task interaction - Yingchao Feng; Xian Sun; Wenhui Diao; Jihao Li; Ruigang Niu; Xin Gao; Kun Fu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Performance and mechanisms for tetrabromobisphenol A efficient degradation in a novel homogeneous advanced treatment based on S2O42− activated by Fe3+ - Wei Song; Mu Li; Sen Xu; Zhuoyue Wang; Ji Li; Xiaolei Zhang; Wenhui Qiu; Zhihong Wang; Qi Song; Kalpana Bhatt; Caixia Fu (Environmental Pollution, 2023)

The state-of-the-art application of functional bacterial cellulose-based materials in biomedical fields - Hanqi Qian; Jingjing Liu; Xucai Wang; Wenhui Pei; Caili Fu; Mingguo Ma; Caoxing Huang (Carbohydrate Polymers, 2023)

Supramolecular self-assembled AIE molecules are used in the search for target proteins in norcantharidin - Lijuan Ma; Xuetong Sun; Wenwen Ji; Bei Zhang; Jianting Li; Wenjuan Fu; Xiangying Zhang; Wenhui Qian; Enze Sheng; Dong Zhu (Analytica Chimica Acta, 2023)

Effects of the neurotoxin β-N-methylamino-L-alanine (BMAA) on the early embryonic development of marine shellfish and fish - Yilei Fu; Aifeng Li; Jiangbing Qiu; Wenhui Yan; Chen Yan; Lei Zhang; Min Li (Frontiers in Marine Science, 2022)
The neurotoxin β - N -methylamino- L -alanine (BMAA) produced by cyanobacteria and diatoms can accumulate in diverse aquatic organisms through the food web. In the present study, embryos of mussel Mytilus galloprovincialis (Lamarck, 1819), oyster Magallana gigas (Thunberg, 1793), and marine medaka Oryzias melastigma (McClelland, 1839) were exposed to BMAA dissolved in seawater and monitored for early developmental effects. Results demonstrated that the embryonic development of mussels and oysters were significantly inhibited when BMAA concentrations were above 100 μg BMAA·HCl/L (0.65 µM) and 800 μg BMAA·HCl/L (5.18 µM), respectively. The shell growth of mussel embryos was also markedly inhibited by BMAA ≥ 100 μg BMAA·HCl/L (0.65 µM). Based on the dose-response curves related to the modified malformation rate of embryos, the median effective concentration (EC 50 ) values of mussel (48 h) and oyster (24 h) embryos were 196 μg BMAA·HCl/L (1.27 µM) and 1660 μg BMAA·HCl/L (10.7 μM), respectively. A sustained and dose-dependent decrease in heart rate was apparent in marine medaka embryos at 9-days post fertilization following BMAA exposure. However, no obvious effect on ATP concentration was noted in these marine medaka embryos. The current study contributes to our understanding of the sublethal effects of BMAA on the early embryonic development of marine bivalves and medaka. Further research examining the long-term effects of BMAA on the early development of marine organisms is necessary to determine seawater quality criteria for protection.

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Spatial–temporal differentiation and influencing factors of marine fishery carbon emission efficiency in China - Yuan Gao; Zhongwei Fu; Jun Yang; Miao Yu; Wenhui Wang (Environment, Development and Sustainability, 2022)

Photocatalysis of aqueous PFOA by common catalysts of In2O3, Ga2O3, TiO2, CeO2 and CdS: influence factors and mechanistic insights - Caixia Fu; Xiuru Xu; Chunmiao Zheng; Xinjie Liu; Dandan Zhao; Wenhui Qiu (Environmental Geochemistry and Health, 2022)

Regulatory relationship between backfill mining and environmental engineering geological patterns induced by underground coal mining - Shiliang Liu; Weiguo Li; Guangsheng Fu; You Zhang; Xinghai Li; Bin Xie; Haodong Zhang; Wenhui Zhang (Arabian Journal of Geosciences, 2021)

Bridge Crack Semantic Segmentation Based on Improved Deeplabv3+ - Huixuan Fu; Dan Meng; Wenhui Li; Yuchao Wang (Journal of Marine Science and Engineering, 2021)
Cracks are the main goal of bridge maintenance and accurate detection of cracks will help ensure their safe use. Aiming at the problem that traditional image processing methods are difficult to accurately detect cracks, deep learning technology was introduced and a crack detection method based on an improved DeepLabv3+ semantic segmentation algorithm was proposed. In the network structure, the densely connected atrous spatial pyramid pooling module was introduced into the DeepLabv3+ network, which enabled the network to obtain denser pixel sampling, thus enhancing the ability of the network to extract detail features. While obtaining a larger receptive field, the number of network parameters was consistent with the original algorithm. The images of bridge cracks under different environmental conditions were collected, and then a concrete bridge crack segmentation data set was established, and the segmentation model was obtained through end-to-end training of the network. The experimental results showed that the improved DeepLabv3+ algorithm had higher crack segmentation accuracy than the original DeepLabv3+ algorithm, with an average intersection ratio reaching 82.37%, and the segmentation of crack details was more accurate, which proved the effectiveness of the proposed algorithm.

A search method for probabilistic critical slip surfaces with arbitrary shapes and its application in slope reliability analysis - Yibiao Liu; Weizhong Ren; Chenchen Liu; Guijun Fu; Wenhui Xu; Simin Cai (Natural Hazards, 2021)

Sucrose signaling function on the formation and swelling of bulblets of Lilium sargentiae E.H. Wilson - Suping Gao; Yuan Zhu; Lingyun Zhou; Xiaofeng Fu; Ting Lei; Qibing Chen; Xiaofang Yu; Yonghong Zhou; Wenji Li; Ju Hu; Di Hu; Wenhui Si (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Red mud-modified biochar reduces soil arsenic availability and changes bacterial composition - Qi Zou; Wenhui An; Chuan Wu; Waichin Li; Anqin Fu; Ruiyang Xiao; Huikang Chen; Shengguo Xue (Environmental Chemistry Letters, 2018)

Shape-based object extraction in high-resolution remote-sensing images using deep Boltzmann machine - Qichang Wu; Wenhui Diao; Fangzheng Dou; Xian Sun; Xinwei Zheng; Kun Fu; Fei Zhao (International Journal of Remote Sensing, 2016)

Geochemistry of Altungol cap dolostones from the Tarim Basin, NW China - Fan Feng; Ping Guan; Wenhui Liu; Wei Zhang; Peixian Liu; Xing Jian; Ling Fu (Arabian Journal of Geosciences, 2016)

Al-induced secretion of organic acid, gene expression and root elongation in soybean roots - Daoming Wu; Man Zhao; Shouying Shen; Youqiang Fu; Takayuki Sasaki; Yoko Yamamoto; Wenhui Wei; Hong Shen (Acta Physiologiae Plantarum, 2013)

Effects of Bacillus preparations on immunity and antioxidant activities in grass carp (Ctenopharyngodon idellus) - Li Weifen; Zhang Xiaoping; Song Wenhui; Deng Bin; Liang Quan; Fu Luoqin; Zheng Jiajia; Wang yue; Yu Dongyou (Fish Physiology and Biochemistry, 2012)

Avian comparative genomics: reciprocal chromosome painting between domestic chicken (Gallus gallus) and the stone curlew (Burhinus oedicnemus, Charadriiformes)—An atypical species with low diploid number - Wenhui Nie; Patricia C. M. O’Brien; Bee L. Ng; Beiyuan Fu; Vitaly Volobouev; Nigel P. Carter; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2009)

Comparative genome maps of the pangolin, hedgehog, sloth, anteater and human revealed by cross-species chromosome painting: further insight into the ancestral karyotype and genome evolution of eutherian mammals - Fengtang Yang; Alexander S. Graphodatsky; Tangliang Li; Beiyuan Fu; Gauthier Dobigny; Jinghuan Wang; Polina L. Perelman; Natalya A. Serdukova; Weiting Su; Patricia CM O'Brien; Yingxiang Wang; Malcolm A. Ferguson-Smith; et al. (Chromosome Research, 2006)

Evolution of Genome Organizations of Squirrels (Sciuridae) Revealed by Cross-Species Chromosome Painting - Tangliang Li; Patricia C. M. O'Brien; Larisa Biltueva; Beiyuan Fu; Jinhuan Wang; Wenhui Nie; Malcolm A. Ferguson-Smith; Alexander S. Graphodatsky; Fengtang Yang (Chromosome Research, 2004)

Refined genome-wide comparative map of the domestic horse, donkey and human based on cross-species chromosome painting: insight into the occasional fertility of mules - Fengtang Yang; Beiyuan Fu; Patricia C. M. O'Brien; Wenhui Nie; Oliver A. Ryder; Malcolm A. Ferguson-Smith (Chromosome Research, 2004)

The genome phylogeny of domestic cat, red panda and five mustelid species revealed by comparative chromosome painting and G-banding - Wenhui Nie; Jinhuan Wang; Patricia C.M. O'Brien; Beiyuan Fu; Tian Ying; Malcolm A. Ferguson-Smith; Fengtang Yang (Chromosome Research, 2002)